2006
DOI: 10.1016/s1556-0864(15)31587-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved Diagnostic Efficacy by Rapid Cytology Test in Fluoroscopy-Guided Bronchoscopy

Abstract: Background: Fluoroscopy-guided bronchoscopy is a safe and routine method used to obtain a histologic or cytologic specimen of peripheral lung nodules, but it has low sensitivity in diagnosing malignant tumors. Although feedback from rapid cytology tests are expected to improve diagnostic rates, the value of the routine use of rapid cytology tests has not been established. Materials and Methods: We prospectively studied 657 patients with suspected peripheral malignant lung lesions on chest computed tomography w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…[1619] It has been previously reported that ROSE had 85-92% and 100% sensitivity and specificity, respectively, when it is used in combination with EMN and PET-CT.[1520] The present study has shown that the combination of EMN and ROSE overcomes the limitations related to obtaining adequate biopsy specimen. Mean pass number was four for MLN and three for PL representing optimal number for such diagnostic work-ups.…”
Section: Discussionmentioning
confidence: 54%
“…[1619] It has been previously reported that ROSE had 85-92% and 100% sensitivity and specificity, respectively, when it is used in combination with EMN and PET-CT.[1520] The present study has shown that the combination of EMN and ROSE overcomes the limitations related to obtaining adequate biopsy specimen. Mean pass number was four for MLN and three for PL representing optimal number for such diagnostic work-ups.…”
Section: Discussionmentioning
confidence: 54%
“…However, Uchida et al. reported that integrating ROSE into bronchoscopic examination for peripheral tumours of size <20 mm improved the diagnostic sensitivity from 63.2% to 86.2% . Conversely, Maekura et al.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our study did not have access to ROSE, which improves diagnostic efficacy independent of localization, lesion histology, and operator experience. 33 However, ROSE is costly and requires a longer procedure time. In addition, ROSE is still not routinely available in many centers, so our results are representative of a large portion of pulmonary practice.…”
Section: Discussionmentioning
confidence: 99%